Extending otology services to the rural community - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Hearing screening services scarcely extend to rural communities due to limited resources. Active intervention to prevent hearing loss may, therefore, be ineffective. Hearing screening with the smartphone may extend screening services to rural communities. This paper aims to assess the reliability of using the smartphone for hearing screening by comparing results obtained with those of a standard calibrated audiometer.Methodology:A hospital-based cross-sectional study of 60 participants consisting of 36 males and 24 females, age ranged from 16 years to 68 years (mean = 33.4, standard deviation = 12.7). Using the Android application ’Hearing Test Pro™’ installed on Samsung Galaxy Note 3 smartphone, hearing threshold across 250 Hz–8000 Hz frequencies of participants was determined in a quiet clinic room. This was repeated using a calibrated Welch/Allyn TM 262 auto tympanometer/audiometer. Hearing thresholds at low, high and speech range frequencies were summarised with threshold >40 dB considered as ’Failed screening’. The results obtained from the two methods were compared.Results:There was complete agreement between the hearing threshold results obtained by the two methods at high frequencies with smartphone sensitivity 96% and specificity 100%. There was a moderate agreement between the two methods at speech range frequencies with smartphone sensitivity 86% and specificity 99%. The least agreement between the two methods was in the low frequencies.Conclusion:The smartphone application ’Hearing test Pro’ is quite accurate, especially in detecting high frequency hearing loss and can be used effectively in hearing screening.